A fermentative approach to ameliorating solid waste challenges within food and hospitality industry - Jamal, Parveen; Saheed, Olorunnisola Kola; Abdulkarim, Mohd Ismail; Alam, Md Zahangir; Muyibi, Suleyman Aremu (Elsevier Ltd., 2015)
Microbial conversion of organic residues into resource often involves growth and development via modification of complex sugars inherent in the residues. Solid state bioconversion (SSB) process involving mixed culture of white rot fungi was conducted. Product synthesis by the microorganisms and bio-degradation of fruit peels' macromolecules were analyzed chemically and structurally. Protein enrichment was higher when fungal strains were mixed together (141.18 mg g-1) compared with when grown at 4 cm apart (115.62 mg g1). Different mixtures of fruit peels raised fermentable sugar composition to 500.99 mg g1 and protein enrichment increased to 160.68 mg g1 while complex carbon was redistributed. Cellulase activity of 1.33 ± 0.04 units ml1 and a-amylase activity of 112.46 ± 0.28 units ml1 were recorded. Fourier transformation infrared (FT-IR) analysis revealed immense modification of complex sugars (cellulose, hemicellulose and lignin) and secretion of simple sugars by filamentous fungi.